Depression, anxiety and stress levels among medical and dental students: а cross sectional study - S. Kumar; S. Jayachandra; S. R. Kodidala (Сибирский научный медицинский журнал, 2022)
Introduction. In medical and dental colleges increased levels of psychological disturbances such as depression, anxiety and stress (DASS) among students which affect the way these students take care of patients. By identifying necessary modifications can be made to improve the quality of life among medical and dental students.The aim of this study is to assess DASS among undergraduate medical and dental students in Mathura city, Uttar Pradesh, India.Material and methods. The medical and dental college students from K.D. Medical College and K.D. Dental College students were included. A short questionnaire version of depression, anxiety and stress scale (DASS-21) was distributed and filled by students. Comparison among the variables was done using independent t-test with significance at p < 0.05.Results. The study group comprised 415 subjects, 164 (39.51 %) males and 251 (60.48 %) females. Among them 297 (71.56 %) were medical students and 118 (28.43 %) were dental students. Out of a total of 297 medical students, the severity of overall DASS score was 38.8 ± 10.2 while depression score was 12.6 ± 4.0, anxiety score was 13.0 ± 4.1, stress score was 13.2 ± 4.3. Out of a total of 118 dental students the severity of overall DASS score was 37.8 ± 11.1 while depression scores was 12.2 ± 4.2, anxiety score was 12.9 ± 4.0, stress score was 12.7 ± 4.5. The overall mean DASS score and its dimensions were not significant based on gender.Conclusions. Clinical years were more stressful than the nonclinical years. This suggests a need for special attention to the structure of the clinical program, particularly at the point of transition from the preclinical to the clinical phase.